Combining immune checkpoint inhibitors with thoracic radiotherapy enhances outcomes in advanced non-small-cell lung cancer: a real-world study - Zou, Yao; Chen, Yichong; Zhou, Xiaojuan; Gong, Youling; Xu, Yong; Zou, Bingwen; Peng, Feng; Huang, Meijuan; Lu, You; Liu, Yongmei (Frontiers in Oncology, 2025)
BackgroundWe aimed to evaluate the efficacy of thoracic radiotherapy (TRT) combined with immune checkpoint inhibitors (ICIs) in patients with advanced non-small-cell lung cancer (NSCLC) in real-world clinical settings and identify predictive subgroups that may benefit most from this approach.MethodsWe retrospectively reviewed the medical records of patients with advanced NSCLC who were treated with ICIs at West China Hospital from January 2015 to May 2022.ResultsA total of 302 patients with advanced NSCLC were included in this study. Among them, 54.3% (164/302) received ICIs in combination with TRT and were assigned to the TRT+ICIs group, while 45.7% (138/302) received ICIs alone and were assigned to the ICIs-only group. The median overall survival (OS) was significantly longer in the TRT+ICIs group (34.7 months) than in the ICIs-only group (27.1 months; P = 0.016). Additionally, the 24-month and 36-month OS rates were notably higher in the TRT+ICIs group (63.7% and 49.0%, respectively) than in the ICIs-only group (55.1% and 16.2%). Subgroup analysis of OS between the TRT+ICIs and ICIs-only groups identified factors associated with improved survival, including male sex, former smoking, Eastern Cooperative Oncology Group (ECOG) performance status 0–1, stage IIIb–c, high albumin level, and low neutrophil-to-lymphocyte (NLR) level. Multivariate analysis identified receipt of TRT, programmed death-ligand 1 (PD-L1) expression < 1%, PD-L1 ≥ 50%, and NLR as statistically significant independent prognostic factors for OS (P < 0.05). The combination treatment was well-tolerated, with an acceptable safety profile.ConclusionOur findings suggest that adding TRT to immunotherapy improves survival outcomes in patients with advanced NSCLC.